(untitled) (American Journal of Islam and Society, 2014)
In honor of World Day of Social Justice, on February 24, 2014, Shia Rights Watch and American University held the first-ever conference devoted to presenting new paradigms for exploring how the rights of the minority Shia Muslim community can be protected against such entrenched realities as subordination, injustice, violence, discrimination, and marginalization. Social scientists define minority as a culturally, ethnically, religiously, or racially distinct group that coexists with, but is subordinate to, a more dominant group. This subordinancy, the chief defining characteristic of any minority, has nothing to do with numbers, a fact perhaps most vividly illustrated by South Africa under apartheid (c. 1950-91). The conference, held at American University, was cosponsored by the Mohammed Said Farsi Chair of Islamic Peace. Well-known and high caliber policymakers, professors, and researchers shared their findings in order to offer solutions designed to foster peace, tolerance, and religious freedom for this group and the regions in which they reside. In his capacity as the first occupant of the endowed Mohammed Said Farsi Chair of Islamic Peace as well as the founder of the university-wide Center for Global Peace, Abdul Aziz Said (School of International Service, American University) welcomed everyone. He remarked that peace is far more than the absence of war, that it is, in fact, inclusive of social justice, ecological sustainability, sustainable economics, and cultural diversity (peace as the absence of structural violence). Thus, conflict resolution is one of the building blocks of peace. Given that the ends we seek and the means that we employ in the study of peace and conflict resolution are interconnected, teaching these two fields must be based on a pedagogy that is itself peace and not merely a process of certification. He argued that education about peace and conflict resolution and education for peace and conflict resolution are two sides of the same coin. Peace and conflict resolution education combine information with liberation and procedure with transformation. He concluded ...